Pengaruh Model Problem Based Learning Berbantuan PowerPoint Interaktif terhadap Kemampuan Pemecahan Masalah Peserta Didik Kelas V SDN 50 Cakranegara - Reza Nurizzaty; Asri Fauzi; Sudirman (Mataram University, 2026)
The mathematical problem-solving ability of fifth-grade students at SDN 50 Cakranegara was still relatively low, as indicated by the preliminary observation showing that 13 out of 26 students in Class Vb were unable to solve mathematical problem-solving tasks accurately. This condition was presumed to be influenced by teacher-centered learning practices and the limited use of interactive learning media. This study aimed to determine the effect of the Problem Based Learning (PBL) model assisted by interactive PowerPoint on the mathematical problem-solving ability of fifth-grade students at SDN 50 Cakranegara. The study employed a quantitative approach using a quasi-experimental method with a Non-Equivalent Control Group Design involving 53 students (27 in the experimental class and 26 in the control class), selected through total sampling. The data were analyzed using the Shapiro–Wilk normality test, Levene’s test for homogeneity, and hypothesis testing. Since three out of four datasets were not normally distributed, the hypothesis was tested using the non-parametric Mann–Whitney U test. The results showed a significance value of < 0.001 (< 0.05), indicating that the null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted. Furthermore, the experimental group achieved a higher mean post-test score (49.85) than the control group (18.92). These findings suggest that integrating the Problem Based Learning model with interactive PowerPoint provides an effective instructional framework for enhancing the mathematical problem-solving ability of elementary school students, who are generally in the concrete operational stage of cognitive development.